About the localization of the village (rustak) of Sanzharfagn. - Aslanov Abduvali Polatovich (Zien Journals, 2023)
The article explores issues related to the localization of Sanjarfagh's fortress in Central Sogdiana, specifically in the regions of Central Sogdiana or Samarkand Sogdiana. It draws on the analysis of ancient sources related to Samarkand Sogdiana and the latest archaeological findings to identify the exact location of Sanjarfagh's fortress. The article also presents the delineation of the fortress's boundaries and the identification of its central position, incorporating the most recent research results
Keywords: Sanjarfagh; Sogd; Urgut; localization